Tantangan dan Solusi dalam Monitoring DPS pada Laznas : Studi Analisis Peraturan Zakat - Ma’ruf, Farid (Al-Tasyree: Jurnal Bisnis, Keuangan dan Ekonomi Syariah, 2024)
Zakat management in Indonesia faces significant challenges related to the interpretation and implementation of the Zakat Law (Law No. 23 of 2011), the effectiveness of the Minister of Religious Affairs regulations, and coordination between Baznas and zakat institutions. These issues include unclear regulations, inconsistent policies, and lack of synergy between related institutions, which hamper the effectiveness of sharia supervision. This study aims to identify the main challenges in zakat management, analyze possible solutions, and provide policy recommendations to improve the effectiveness of sharia supervision and zakat management in Indonesia. The research method used is a qualitative approach with documentation study techniques and critical analysis. Data were collected from literature, annual reports, official documents, and related regulations such as the Zakat Law, Minister of Religious Affairs regulations, and Baznas regulations. Analysis was conducted to evaluate issues in regulations, DPS competency, and support from zakat institutions. This study found that the main challenges lie in the interpretation of regulations, inconsistent implementation, and lack of coordination between zakat institutions. Recommended solutions include revising regulations to improve legal clarity, collaborating with external parties to enrich supervision, and implementing modern technology for monitoring efficiency. Recommendations for the government and Baznas include strengthening the capacity and independence of the Sharia Supervisory Board (DPS), as well as increasing transparency through technology. The implementation of these recommendations is expected to increase the effectiveness of zakat management and its benefits for the community.